2018
DOI: 10.1371/journal.pone.0205086
|View full text |Cite
|
Sign up to set email alerts
|

Child sexual abuse in India: A systematic review

Abstract: ObjectiveChild Sexual Abuse (CSA) is a pressing human right issue and public health concern. We conducted a systematic review of quantitative and qualitative studies published in the past decade on CSA in India to examine the distribution of the prevalence estimates for both genders, to improve understanding of the determinants and consequences of CSA and identify gaps in the current state of research.MethodsFor this systematic review, we searched electronic literature databases (PubMed, POPLINE, and PsycINFO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
96
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(107 citation statements)
references
References 83 publications
6
96
3
2
Order By: Relevance
“…It is also worth noting that female children and adolescents were more likely to experience sexual violence, corroborating several other studies in the literature (13)(14)(15)(16)(17)(19)(20)(21)(22)(23)(24) and reinforcing the evidence regarding the fragility of females in gender relations, whether arising from the superior physical strength of men, the inequality in gender relations and vulnerability, or the risk of women experiencing violence, especially if they are children and adolescents (7) .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It is also worth noting that female children and adolescents were more likely to experience sexual violence, corroborating several other studies in the literature (13)(14)(15)(16)(17)(19)(20)(21)(22)(23)(24) and reinforcing the evidence regarding the fragility of females in gender relations, whether arising from the superior physical strength of men, the inequality in gender relations and vulnerability, or the risk of women experiencing violence, especially if they are children and adolescents (7) .…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence of sexual violence against children and adolescents was similar to other data in the literature, unveiling the magnitude of this problem and its higher occurrence among females (13)(14)(15) . Data published by the WHO, based on studies carried out in regions such as Africa, Asia and Australia, estimated that the prevalence of sexual abuse by gender was 18% for girls and 8% for boys (16) .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Luo and colleagues 2007 found higher rates of abuse among Chinese men (5.1%) compared to women (3.3%) and commented that the observed pattern contrasted with the typical pattern in the west which has a higher prevalence for women than for men and found that the prevalence for Chinese men was within the 3% -10% prevalence for men in the west and that the prevalence for Chinese women was far lower than the typical 10% -20% for women in the west (Luo et al, 2008). This is also the case in some studies in India were young boys were found to have similar and sometimes higher prevalence of CSA as girls (Choudhry et al, 2018). The culture within Asian communities may explain this rather Open Journal of Social Sciences untypical pattern.…”
Section: Discussionmentioning
confidence: 81%
“…Child sexual abuse has been linked to numerous maladaptive health behaviors, and poor social, mental and physical health outcomes throughout the lifespan. 7 Serotonin abnormalities have been reported in various studies among participants exposed to child sexual abuse. Structures such as the prefrontal cortex, superior temporal gyrus, corpus callosum, parietal lobes, hippocampus, and cerebellum were found to demonstrate volumetric and structural changes in response to the trauma of child sexual abuse.…”
Section: Discussionmentioning
confidence: 99%